The Relative Contributions of Social-Personality Traits, Cognitive Learning Factors and SAT Scores to Grade Point Average - Brenda Hannon (An Overview of Literature, Language and Education Research Vol. 5, 2024)
To date, studies have simultaneously examined the relative predictive powers of two or three factors on GPA (Grade Point Average). However, because GPA is such an important benchmark of academic success, further investigation is warranted in order to further our practical and theoretical understanding. The present study examines the relative powers of five social/personality factors, five cognitive/learning factors, and SAT (Scholastic Assessment Test) scores to predict freshmen and non-freshmen (sophomores, juniors, seniors) academic success (i.e., GPA). All factors were assessed using psychometric measures. The results revealed many significant predictors of GPA for both freshmen and non-freshmen. However, subsequent regressions, which systematically analysed the contributions of social/personality factors, cognitive/learning factors, and SAT scores on GPA, showed that only academic self-efficacy, epistemic belief of learning, and high-knowledge integration, which is an individual’s ability to integrate new information with prior knowledge, explained unique variance in GPA (19%-freshmen and 23.2%-non-freshmen). Further, for freshmen, SAT scores explained an additional unique 10.6% variance after the influences attributed to these three predictors were removed whereas for non-freshmen, SAT scores failed to explain any additional variance. These results highlight the unique and important contributions of academic self-efficacy, epistemic belief of learning and high-knowledge integration to GPA beyond other previously-identified predictors. They also suggest that future research should conceptualize GPA as a multi-faceted construct that can only truly be understood by integrating multiple content areas.